Climate change, food and nutrition policies in Uganda: Are they gender- and nutrition-sensitive - Bamanyaki, Patricia A. (International Food Policy Research Institute, 2020)
According to the 2018 Global Hunger Index (GHI), hunger among Uganda’s population has risen, evidenced by a score of 31.2 compared to a score of 26.4 in 2016. Despite being acclaimed as the “regional food basket” for East Africa, Uganda’s GHI score is higher than its immediate neighbors’ (Kenya, 23.3; Tanzania, 29.5; and Rwanda, 28.7) and the sub-Saharan Africa regional average of 29.4 (GHI 2018). Whereas improvements have been registered in child nutrition and mortality indicators over the years from 2012 to 2017 (prevalence of stunting reduced from 34 to 29 percent; wasting from 5 to 4 percent; and under- five mortality from 8 to 5 percent), the proportion of the population that is undernourished grew from 31 percent during the period 2009–2010 to 41 percent during the period 2015–2017 (GHI 2018). Obesity among adults aged 18 years and above also rose from 5.8 percent in 2012 to 7.1 percent in 2016.